Retreat or Entrenchment? Drug Policies in the Nordic Countries at a Crossroads - Tham, Henrik (Stockholm Studies in Social Policy and Welfare, 2021)
The drug policies of the Nordic countries have been relatively strict. Since this seems to contradict the internationally recognized liberal criminal policy in general, analyses have been devoted to try to understand this gap. Why doesn't the "Scandinavian exceptionalism" apply to the drug policies? The new question in relation to drug policy is, however, if and how the Nordic countries will adapt to a situation when several countries all over the world are questioning 'the war on drugs' and orienting themselves in the direction of decriminalization and legalization. An analysis of a possible change in drug policies must be undertaken against the background of the existing policies. There are both similarities and differences between the five countries. A common feature is a stress on the demand side through both treatment and punishments directed against the user and abuser. Differences are shown in degrees of toughness in drug policies with Sweden strongest stressing a zero-tolerance stand and Denmark being the most liberal in the Nordic context. The strong welfare state ideology of all the countries is important for understanding the obstacles to a more liberal and permissive drug policy. The welfare state is an interventionist state. To not do anything about what is considered to be a problem both for the individual and the society is just not an option. In most of the countries the traditions from the temperance movements also have influenced the drug policies through the stepping-stone or gateway theory, not making a distinction between soft and hard drugs. At the same time, a number of facts and processes work in the direction of change. The drug policies of the countries have not delivered, including high numbers of drug-related deaths. The debate has opened up in just a short period of time. Many of the political youth parties demand decriminalisation of use of drugs and so have some public authorities. Human rights arguments are increasingly being put forward as a critique of police interventions. A tendency for politicians to meet the critique seems to be to separate the marginal abuser from the recreational user. The first one should be given treatment and care according to welfare state ideology. The second one, however, could be punished since the user in line with neo-liberal theory can choose and by the use contributes to the drug trade and even the killings in poor suburbs. The Nordic countries stand at a crossroads, but what new roads will be taken is far from clear.